Integrated Nutrition and Physical Activity Program Based on Social Cognitive Theory to Enhance Quality of Life, Nutritional Status, and Physical Activity in Older Adults - Ruhayati, Yati; Suherman, Adang; Zaky, Mohammad; Rahayu, Nur Indri (Universitas Pendidikan Indonesia (UPI), 2025)
Population aging in Indonesia demands scalable programs that elevate everyday functioning and well-being. This study evaluated an integrated nutrition and physical activity program grounded in Social Cognitive Theory for community-dwelling older adults. Using a quasi-experimental, community-based design, the intervention combined nutrition education with cooking practice, progressive exercise, self-efficacy-oriented counselling, and peer support, and was assessed with validated measures of quality of life, nutritional status, and physical activity. Participants receiving the program achieved marked improvements across all outcomes relative to comparison participants, and gains persisted beyond the intervention period. These benefits arose because the program simultaneously strengthened capability through skills and knowledge, opportunity through social support and access, and motivation through enhanced self-efficacy, goal setting, and self-monitoring. Hands-on practice and vicarious learning built mastery, while culturally adapted materials and peer leaders reduced barriers and reinforced adherence. Findings indicate that a theory-driven, multi-component approach is feasible within primary care and can advance healthy aging and equity in Indonesian communities.